2014
DOI: 10.1242/jcs.133892
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Src trafficking and activation by the endocytic regulatory proteins MICAL-L1 and EHD1

Abstract: Localization of the non-receptor tyrosine kinase Src to the cell periphery is required for its activation and to mediate focal adhesion turnover, cell spreading and migration. Inactive Src localizes to a perinuclear compartment and the movement of Src to the plasma membrane is mediated by endocytic transport. However, the precise pathways and regulatory proteins that are responsible for SRC transport are incompletely understood. Here, we demonstrate that Src partially colocalizes with the endocytic regulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 55 publications
(69 reference statements)
2
16
1
Order By: Relevance
“…It is well known that healthy people have cells with oncogenic K-Ras in different organs at rates far exceeding the rates of cancer development, and Magliano and Lonsdon (2013) report that the presence of oncogenic KRAS is not sufficient to transform cells, but the mechanism that removes barriers to tumorigenesis, is unknown48. Therefore, the perinuclear region as a periphery of the core nucleus may serve as a restriction site for potentially oncogenic proteins such as Ras or as was shown recently for Src8 or for the regulation of tumor suppressor proteins such as p53. In these experiments Src was localized exclusively in the perinuclear region.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that healthy people have cells with oncogenic K-Ras in different organs at rates far exceeding the rates of cancer development, and Magliano and Lonsdon (2013) report that the presence of oncogenic KRAS is not sufficient to transform cells, but the mechanism that removes barriers to tumorigenesis, is unknown48. Therefore, the perinuclear region as a periphery of the core nucleus may serve as a restriction site for potentially oncogenic proteins such as Ras or as was shown recently for Src8 or for the regulation of tumor suppressor proteins such as p53. In these experiments Src was localized exclusively in the perinuclear region.…”
Section: Discussionmentioning
confidence: 99%
“…Tubulation of the Rab8a-dependent recycling system, which is responsible for recycling of non-clathrin-dependent endocytosed cargoes, such as MHC Class I, is regulated by MICAL-L1 [7,8]. MICAL-L1 recruits both Arf6 and EHD1 to recycling membranes and promotes tubulation [7,9,10 • ,11]. The association of MICAL-L1 with tubular endosomes is regulated by Rab35 [8,12].…”
Section: The Recycling Endosome Is a Dynamic Structurementioning
confidence: 99%
“…Recently, we demonstrated that endogenous Src decorates MICAL-L1 tubules in HeLa cells, suggesting that Src is either a cargo or regulator of MICAL-L1-decorated TRE(54). Given that inactive Src overlaps in its localization with transferrin receptor, a bona-fide cargo protein of the ERC, this suggests that Src is likely a cargo.…”
Section: Body Of Reviewmentioning
confidence: 99%
“…This coincides with an increase in Src activation as measured by Src pY416, in agreement with previous findings(44). MICAL-L1- or EHD1-depletion caused Src to remain in the ERC following EGF treatment and also severely impaired Src activation(54). MICAL-L1-depletion in human fibroblasts decreased PDGF- and integrin-induced Src activation and also impaired Src-dependent processes such as PDGF-induced macropinocytosis, focal adhesion turnover, cell spreading and migration(54).…”
Section: Body Of Reviewmentioning
confidence: 99%
See 1 more Smart Citation